C90 high-strength low-carbon concrete and its preparation method and casting method
By using cement, vitrified microbeads, aggregate and other materials with specific ratios in concrete, the problem that existing concrete is difficult to meet high strength and good working performance at the same time is solved, and high strength and excellent durability and apparent quality are achieved.
Patent Information
- Application Number
- CN202510137490.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-01
AI Technical Summary
It is difficult for existing concrete to meet high strength and good working performance at the same time, especially in applications such as wind power towers.
C90 high-strength low-carbon concrete is used, and its raw materials include cement, vitrified microbeads, aggregate, water reducer, water, gas induction agent and calcium nitrate. Through the hydration reaction of cement and water and the synergistic effect of vitrified microbeads and other materials, the viscosity, easiness and anti-seepage and frost resistance of concrete are improved.
The compressive strength of concrete at 28 days is achieved, and the apparent quality, mechanical properties and durability of concrete are improved, and the surface bubbles and cracks are reduced.
Smart Images

Figure BDA0005263729430000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a C90 high-strength low-carbon concrete and a preparation method and a casting method thereof. Background Art
[0002] At present, the design height of wind turbine towers is getting higher and higher, and the original steel structure towers can no longer meet the demand, especially with the gradual maturity of wind turbine concrete tower technology and the gradual expansion of the market scale. In addition, different mixed tower systems have different requirements for concrete. The mixed tower top ring and vertical mold mixed tower segments require high strength of concrete while also requiring the concrete to have low viscosity, long setting time, small slump loss, good collapse protection effect, few bubbles and good surface quality.
[0003] Therefore, the concrete in the prior art can no longer meet both strength and workability requirements. Summary of the invention
[0004] The present invention provides a C90 high-strength low-carbon concrete and a preparation method and a casting method thereof, which are used to solve the problem that the concrete in the prior art is difficult to meet both strength and workability requirements.
[0005] In a first aspect, the present invention provides a C90 high-strength low-carbon concrete, wherein the raw materials of the C90 high-strength low-carbon concrete include, by mass, 420 to 480 parts of cement, 120 to 150 parts of vitrified microspheres, 1640 to 1880 parts of aggregate, 12 to 14.1 parts of a water reducer, 110 to 130 parts of water, 0.025 to 0.055 parts of an air entraining agent, and 0.5 to 1.5 parts of calcium nitrate; the compressive strength of the C90 high-strength low-carbon concrete at 28 days of age is not less than 100 MPa.
[0006] Compared with the prior art, the advantages of the present invention are as follows: the C90 high-strength low-carbon concrete provided by the present invention, through the hydration reaction of cement and water, aggregates playing a skeleton role are cemented together, and then through the synergistic effect of vitrified microspheres, water reducers, air entraining agents and calcium nitrate, the viscosity, workability and anti-seepage and anti-freezing properties of the concrete are jointly improved, and surface bubbles are reduced, concrete cracks are eliminated, the apparent quality is better, and at the same time, the mechanical properties and durability are good, and the compressive strength at the age of 28 days is not less than 100MPa.
[0007] Furthermore, the cement is P.O52.5R cement.
[0008] Furthermore, the combustion grade of the vitrified microspheres is A1, the water requirement is not more than 100%, the 7d activity index is not less than 80%, and the 28d activity index is not less than 100%.
[0009] Furthermore, the aggregate comprises coarse aggregate and fine aggregate in a mass ratio of (1080-1200):(560-680), the particle size of the coarse aggregate is 5-25 mm, and the fineness modulus of the fine aggregate is 2.2-2.6.
[0010] Further, the coarse aggregate comprises crushed stone, and the content of needle-like particles in the aggregate is not more than 6%; and / or,
[0011] The fine aggregate comprises river sand and machine-made sand in a mass ratio of (5-7):(3-5), the fineness modulus of the river sand is 2.3-2.6, and the fineness modulus of the machine-made sand is 2.2-2.5.
[0012] Furthermore, the water reducing agent has a water reducing rate of not less than 25%; and / or,
[0013] The water reducing agent is a polycarboxylic acid water reducing agent; and / or,
[0014] The air-entraining agent is a rosin air-entraining agent; and / or,
[0015] The particle size of the calcium nitrate is not greater than 3 mm.
[0016] In a second aspect, the present invention provides a method for preparing C90 high-strength low-carbon concrete, which is used to prepare the C90 high-strength low-carbon concrete described in the first aspect, comprising the following steps:
[0017] A raw material system including 420-480 parts of cement, 120-150 parts of vitrified microspheres, 1640-1880 parts of aggregate, 12-14.1 parts of water reducer, 110-130 parts of water, 0.025-0.055 parts of air entraining agent and 0.5-1.5 parts of calcium nitrate is mixed and stirred to obtain the C90 high-strength low-carbon concrete.
[0018] Further, the following steps are included:
[0019] (1) weighing the cement, the vitrified microspheres, and the aggregate, mixing them and putting them into a mixer, and performing a first stirring process to obtain a dry material component;
[0020] (2) adding the water reducing agent and 3 / 4 of the water to the dry material component, performing a second stirring process, and obtaining a wet material component;
[0021] (3) adding the air entraining agent, the calcium nitrate and the remaining water to the wet material component, and sequentially performing a third mixing treatment and a curing treatment to obtain the C90 high-strength low-carbon concrete.
[0022] In a third aspect, the present invention provides a method for casting the C90 high-strength low-carbon concrete according to the first aspect, comprising the following steps:
[0023] (1) using the C90 high-strength low-carbon concrete to perform layered pouring to obtain N layers, wherein N≥1;
[0024] (2) vibrating the poured N layer; the vibrating treatment includes vibrating with an attached vibrator and vibrating with a vibrating rod, wherein the vibrating rod is inserted into the poured (N-1) layer in a vertical direction;
[0025] (3) Repeat steps (1) and (2) until the pouring of C90 high-strength low-carbon concrete is completed.
[0026] Further, the vibrator treatment includes using a 70 vibrator to vibrate the poured N layer, and using a 50 vibrator to vibrate the poured (N-1) layer; and / or,
[0027] When vibrating the poured N layer, an attached vibrator and a vibrating rod are used to synchronously vibrate the poured (N-3) layer; and / or,
[0028] The vibration treatment time is 30 to 50 seconds; and / or,
[0029] The vibrating rod is inserted into the pouring (N-1) layer to a depth of 10 to 20 cm in the vertical direction; and / or,
[0030] In the vibrator treatment, the vibrators adjacent to each other in the horizontal direction are 15 to 20 cm apart; and / or,
[0031] The vibrating rods are distributed in a W shape in the casting surface; and / or,
[0032] The pouring height of each layer in the layered pouring process is 30 to 40 cm. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In a first aspect, the present invention provides a C90 high-strength low-carbon concrete, wherein the raw materials of the C90 high-strength low-carbon concrete include, by mass, 420 to 480 parts of cement, 120 to 150 parts of vitrified microspheres, 1640 to 1880 parts of aggregate, 12 to 14.1 parts of a water reducer, 110 to 130 parts of water, 0.025 to 0.055 parts of an air entraining agent, and 0.5 to 1.5 parts of calcium nitrate; the compressive strength of the C90 high-strength low-carbon concrete at 28 days of age is not less than 100 MPa.
[0035] The C90 high-strength low-carbon concrete provided by the present invention uses a hydration reaction between cement and water to bind aggregates that play a skeleton role, and then uses the synergistic effect of vitrified microspheres, a water reducer, an air entraining agent and calcium nitrate to jointly improve the viscosity, workability and anti-seepage and anti-freezing properties of the concrete, reduce surface bubbles, eliminate concrete cracks, and have better apparent quality. At the same time, the mechanical properties and durability are good, and the compressive strength at the age of 28 days is not less than 100MPa.
[0036] Specifically, the cement is P.O52.5R cement, which further improves the strength and frost resistance, impermeability and wear resistance of the concrete.
[0037] Furthermore, the combustion grade of the vitrified microspheres is A1, the water requirement is not more than 100%, the 7d activity index is not less than 80%, and the 28d activity index is not less than 100%. The vitrified microspheres are spherical, and by further limiting the physical and chemical properties of the vitrified microspheres, they can further play a lubricating role, increase the fluidity of concrete and further reduce the viscosity of concrete.
[0038] In a specific embodiment, the aggregate includes coarse aggregate and fine aggregate in a mass ratio of (1080-1200):(560-680), the particle size of the coarse aggregate is 5-25 mm, and the fineness modulus of the fine aggregate is 2.2-2.6.
[0039] The coarse aggregate includes crushed stone, and the content of needle-shaped particles in the aggregate is not more than 6%, which can further reduce the voids in the concrete and improve the strength and working performance of the concrete.
[0040] Furthermore, the fine aggregate comprises river sand and machine-made sand in a mass ratio of (5-7):(3-5), the fineness modulus of the river sand is 2.3-2.6, and the fineness modulus of the machine-made sand is 2.2-2.5.
[0041] By further defining the particle size and fineness distribution of aggregates in concrete, the durability, strength and workability of concrete can be further improved.
[0042] In a specific embodiment, the water reducing agent has a water reducing rate of not less than 25%, and the water reducing agent is a polycarboxylic acid water reducing agent, which can further improve the workability of concrete, reduce the slump loss of concrete, and enhance the synergistic effect with air entraining agent and calcium nitrate.
[0043] In another specific embodiment, the air entraining agent is a rosin air entraining agent, which can further ensure that the air content in the concrete is maintained at 3%-5%, reduce the viscosity of the concrete and increase the fluidity of the concrete, improve the vibration effect of the vibrating rod, make the concrete surface quality better, and reduce air bubbles and pores.
[0044] Furthermore, the particle size of the calcium nitrate is not greater than 3 mm. The inventors have found that the use of powdered calcium nitrate is more conducive to the dissolution of calcium nitrate in water, which can further improve the early strength of concrete, especially the 1d strength, and enhance the strength and workability of concrete.
[0045] In a second aspect, the present invention provides a method for preparing C90 high-strength low-carbon concrete, which is used to prepare the C90 high-strength low-carbon concrete described in the first aspect, comprising the following steps:
[0046] A raw material system including 420-480 parts of cement, 120-150 parts of vitrified microspheres, 1640-1880 parts of aggregate, 12-14.1 parts of water reducer, 110-130 parts of water, 0.025-0.055 parts of air entraining agent and 0.5-1.5 parts of calcium nitrate is mixed and stirred to obtain the C90 high-strength low-carbon concrete.
[0047] Furthermore, the preparation method of C90 high-strength low-carbon concrete comprises the following steps:
[0048] (1) weighing the cement, the vitrified microspheres, and the aggregate, mixing them and putting them into a mixer, and performing a first stirring process to obtain a dry material component;
[0049] (2) adding the water reducing agent and 3 / 4 of the water to the dry material component, performing a second stirring process, and obtaining a wet material component;
[0050] (3) adding the air entraining agent, the calcium nitrate and the remaining water to the wet material component, and sequentially performing a third mixing treatment and a curing treatment to obtain the C90 high-strength low-carbon concrete.
[0051] By weighing and adding materials in the above-defined sequential step-by-step manner, the strength and durability of concrete can be further enhanced, the working performance and construction performance can be improved, bubbles can be reduced, and the surface quality can be further improved.
[0052] Specifically, the calcium nitrate is a calcium nitrate solution, and the concentration of the calcium nitrate solution is 4% to 11%.
[0053] Furthermore, the first stirring treatment time is 20s to 30s, and the rotation speed is 35 to 40rpm;
[0054] The second stirring treatment time is 50s to 70s, and the rotation speed is 40 to 45rpm;
[0055] The second stirring treatment lasts for 100s to 130s, and the rotation speed is 45 to 50rpm.
[0056] In a third aspect, the present invention provides a method for casting the C90 high-strength low-carbon concrete of the first aspect, comprising the following steps:
[0057] (1) using the C90 high-strength low-carbon concrete to perform layered pouring to obtain N layers, wherein N≥1;
[0058] (2) vibrating the poured N layer; the vibrating treatment includes vibrating with an attached vibrator and vibrating with a vibrating rod, wherein the vibrating rod is inserted into the poured (N-1) layer in a vertical direction;
[0059] (3) Repeat steps (1) and (2) until the pouring of C90 high-strength low-carbon concrete is completed.
[0060] The pouring method provided by the present invention adopts a layered pouring and layered vibration method, and adopts a vibration method combining an attached vibrator and a vibrating rod. The vibrating is performed as the pouring is performed. After the lower layer is poured and vibrated, the vibrating rod needs to be inserted into the lower layer when the upper layer is vibrated, so that the upper and lower layers of concrete are fully integrated, thereby improving the vibration effect. The method is particularly suitable for the C90 high-strength low-carbon concrete described in the first aspect, and can further improve the strength and surface smoothness of the concrete after molding, reduce the occurrence of bubbles, eliminate cracks, and improve the apparent quality.
[0061] Furthermore, the vibrator treatment includes vibrating the poured N layers with a 70 vibrator and vibrating the poured (N-1) layers with a 50 vibrator. Those skilled in the art will know that a 70 vibrator refers to a vibrator with a vibrator head diameter of 70 mm, and a 50 vibrator refers to a vibrator with a vibrator head diameter of 50 mm. By using different types of vibrators in combination, the density and strength of the concrete can be further improved, and quality problems such as bubbles, honeycombs, and rough surfaces in the concrete can be reduced.
[0062] In a specific embodiment, the vibration treatment time of each layer is 30 to 50 seconds, the vibrating rod is inserted into the pouring (N-1) layer to a depth of 10 to 20 cm in the vertical direction; the vibrating rods adjacent to each other in the horizontal direction during the vibrating rod treatment are 15 to 20 cm apart; the vibrating rods are distributed in a W shape on the pouring surface; and the pouring height of each layer in the layered pouring treatment is 30 to 40 cm.
[0063] When vibrating the poured N layer, the poured (N-3) layer is synchronously vibrated using an attached vibrator and a vibrating rod; the poured (N-3) layer is synchronously vibrated using an attached vibrator and a vibrating rod, the attached vibrator and the vibrating rod are turned on at the same time, the vibrating of the vibrating rod is carried out in accordance with claim 10, and the vibration of the attached vibrator is carried out until the pouring of the current layer of concrete is completed.
[0064] By limiting the above-mentioned specific execution parameters, the upper and lower layers of concrete can be further fully integrated, bubbles can be reduced, cracks can be eliminated, the surface quality of concrete can be improved, and the strength and working performance of concrete can be further improved.
[0065] Hereinafter, a C90 high-strength low-carbon concrete provided by the present invention is introduced in detail through specific embodiments.
[0066] Example 1
[0067] (1) Weigh 450 kg of P.O52.5R cement, 150 kg of vitrified microspheres, 1100 kg of coarse aggregate, and 650 kg of fine aggregate, mix them into a mixer, and perform a first stirring process at a speed of 40 rpm for 20 seconds to obtain a dry material component;
[0068] Among them, the combustion grade of the vitrified microspheres is A1, the water requirement is 96%, the 7d activity index is 85%, and the 28d activity index is 105%;
[0069] The particle size of the coarse aggregate is 5 to 25 mm, and the fine aggregate includes river sand and machine-made sand in a mass ratio of 7:3, the fineness modulus of the river sand is 2.3 to 2.6, and the fineness modulus of the machine-made sand is 2.2 to 2.5;
[0070] (2) adding 13 kg of the polycarboxylic acid water reducer and 90 kg of water to the dry material component, and performing a second stirring treatment at a rotation speed of 45 rpm for 60 seconds to obtain a wet material component;
[0071] (3) Add 0.035 kg of rosin air entraining agent, 1.2 kg of calcium nitrate powder and the remaining 30 kg of water to the wet material component, perform a third stirring treatment at a rotation speed of 48 rpm for 120 s, and perform a standard curing treatment for 28 days to obtain the C90 high-strength low-carbon concrete.
[0072] Example 2
[0073] The difference between this embodiment and embodiment 1 is that the water requirement of the vitrified microspheres is 105%.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is that the amount of coarse aggregate added is 1240 kg, and the amount of fine aggregate added is 510 kg.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that the fineness modulus of the fine aggregate is 3.0.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the added amount of the vitrified microspheres is 90 kg.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that the amount of polycarboxylic acid water reducer added is 11.5 kg.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 1 is that the added amount of the rosin air-entraining agent is 0.06 kg.
[0084] Comparative Example 4
[0085] This comparative example is compared with Example 1, the difference is that the addition amount of calcium nitrate powder is 2.1kg.
[0086] Test Example 1
[0087] The concrete prepared in the above examples and comparative examples was subjected to performance tests, and the test results are shown in Table 1.
[0088] Table 1
[0089]
[0090] The C90 high-strength low-carbon concrete provided by the present invention uses a hydration reaction between cement and water to bind aggregates that play a skeleton role, and then uses the synergistic effect of vitrified microspheres, a water reducer, an air entraining agent and calcium nitrate to jointly improve the viscosity, workability and anti-seepage and anti-freezing properties of the concrete, reduce surface bubbles, eliminate concrete cracks, and have better apparent quality. At the same time, the mechanical properties and durability are good, and the compressive strength at the age of 28 days is not less than 100MPa.
[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein by equivalents. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the protection scope of the present invention.
Claims
1. A C90 high-strength low-carbon concrete, characterized in that: The raw materials of the C90 high-strength low-carbon concrete include, by mass, 420-480 parts of cement, 120-150 parts of vitrified microspheres, 1640-1880 parts of aggregate, 12-14.1 parts of water reducer, 110-130 parts of water, 0.025-0.055 parts of air entraining agent and 0.5-1.5 parts of calcium nitrate; the compressive strength of the C90 high-strength low-carbon concrete at the age of 28 days is not less than 100 MPa.
2. The C90 high-strength low-carbon concrete according to claim 1, characterized in that: The cement is P.O52.5R cement.
3. The C90 high-strength low-carbon concrete according to claim 1, characterized in that: The combustion grade of the vitrified microspheres is A1, the water requirement is not more than 100%, the 7d activity index is not less than 80%, and the 28d activity index is not less than 100%.
4. The C90 high-strength low-carbon concrete according to claim 1, characterized in that: The aggregate comprises coarse aggregate and fine aggregate in a mass ratio of (1080-1200):(560-680), the particle size of the coarse aggregate is 5-25 mm, and the fineness modulus of the fine aggregate is 2.2-2.
6.
5. The C90 high-strength low-carbon concrete according to claim 4, characterized in that: The coarse aggregate comprises crushed stone, and the content of needle-like particles in the aggregate is not more than 6%; and / or, The fine aggregate includes river sand and machine-made sand in a mass ratio of (5-7):(3-5), the fineness modulus of the river sand is 2.3-2.6, and the fineness modulus of the machine-made sand is 2.2-2.
5.
6. The C90 high-strength low-carbon concrete according to any one of claims 1 to 5, characterized in that: The water reducing agent has a water reducing rate of not less than 25%; and / or, The water reducing agent is a polycarboxylic acid water reducing agent; and / or, The air-entraining agent is a rosin air-entraining agent; and / or, The particle size of the calcium nitrate is no more than 3 mm.
7. A method for preparing C90 high-strength low-carbon concrete, used for preparing the C90 high-strength low-carbon concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: A raw material system including 420-480 parts of cement, 120-150 parts of vitrified microspheres, 1640-1880 parts of aggregate, 12-14.1 parts of water reducer, 110-130 parts of water, 0.025-0.055 parts of air entraining agent and 0.5-1.5 parts of calcium nitrate is mixed and stirred to obtain the C90 high-strength low-carbon concrete.
8. The method for preparing C90 high-strength low-carbon concrete according to claim 7, characterized in that: The following steps are involved: (1) weighing the cement, the vitrified microspheres, and the aggregate, mixing them and putting them into a mixer, and performing a first mixing process to obtain a dry material component; (2) adding the water reducing agent and 3 / 4 of the water to the dry material component, performing a second stirring process, and obtaining a wet material component; (3) adding the air entraining agent, the calcium nitrate and the remaining water to the wet material component, and sequentially performing a third mixing process and a curing process to obtain the C90 high-strength low-carbon concrete.
9. A method for casting C90 high-strength low-carbon concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Using the C90 high-strength low-carbon concrete to perform layered pouring to obtain N layers, where N ≥ 1; (2) vibrating the poured N layer; the vibrating treatment includes vibrating with an attached vibrator and vibrating with a vibrating rod, wherein the vibrating rod is inserted into the poured (N-1) layer in a vertical direction; (3) Repeat steps (1) and (2) until the pouring of C90 high-strength low-carbon concrete is completed.
10. The method for pouring C90 high-strength low-carbon concrete according to claim 9, characterized in that: The vibrator treatment includes vibrating the poured N layers with a 70 vibrator and vibrating the poured (N-1) layers with a 50 vibrator; and / or, When vibrating the poured N layer, an attached vibrator and a vibrating rod are used to synchronously vibrate the poured (N-3) layer; and / or, The vibration treatment time is 30~50s; and / or, The vibrating rod is inserted into the pouring (N-1) layer to a depth of 10-20 cm in the vertical direction; and / or, During the vibrating rod treatment, adjacent vibrating rods in the horizontal direction are 15 to 20 cm apart; and / or, The vibrating rods are distributed in a W shape in the casting surface; and / or, The pouring height of each layer in the layered pouring process is 30~40cm.